Rancang Bangun Sistem Informasi Pengelolaan Data Transaksi Berbasis Website Pada Ester Laundry - Hartono, Timothy Priambodo; Kristianti, Novera; Putra, Putu Bagus Adidyana Anugrah (Journal of Information Technology and Computer Science, 2023)
Ester Laundry is a laundry service business located in Palangkaraya City, specifically at Jl. G. Obos VIII Gg. Bakung 2 BTN No. 07. Currently, Ester Laundry uses a manual system to manage transaction data without a database storage system, and customers face difficulties in obtaining up-to-date information when picking up their laundry. To address this issue, the development of a Transaction Data Management Information System is proposed. The Waterfall methodology is utilized, involving stages of analysis, design, implementation, testing, and development. The system is designed as a website using PHP, JavaScript, along with the Bootstrap and CodeIgniter frameworks, with MySQL as the database. Black Box testing is conducted to evaluate the website's functionality. The results of the Black Box testing indicate that the Transaction Data Management Website can assist Ester Laundry in processing transaction data and provide benefits to both the business owner and customers. With this system in place, the management of transaction data becomes more efficient and effective, while customers can obtain more accurate laundry information.